Enhancing oral communication skills using mobile phones among undergraduate english language learners in Malaysia - Darmi, Ramiza (SPRINGER, 2017)
The study introduced the use of mobile phones in an English language learning course to second-language learners studying at a higher-education institution in Malaysia. Mobile phones have multifunctional capabilities that can be used anytime and anywhere at the convenience of the learners; therefore, the study aimed to investigate the possibility of using mobile phones as tools to improve the oral interaction skills of the learners. The study explored the basic functions built into mobile phones relevant for an oral communication skills course. A class of 50 learners was assigned as the treatment group and another class of 26 learners as the no treatment group. The treatment group was introduced to the audio recording devices in mobile phones and encouraged to practice the tasks assigned before the evaluation. This study adopted a quantitative research design, and the tools employed were a survey questionnaire and the course assessments. Data in the classroom were collected over a 10-week period. The findings demonstrated an increase in the performance of the learners at the end of the semester; nevertheless, the results must be interpreted with caution as use of mobile phones only started in week 5 of the 10-week semester which may not have given learners sufficient time to master the skills required to use them optimally for language learning..